An efficient sodium citrate-promoted synthetic method for the preparation of AuNPs@mesoSiO2 for surface enhanced Raman spectroscopy in the detection of diluted blood - Yun Zou; Feiyu Yang; Xiaoliang Yuan; Ke Ma; Hui Li; Xuejun Zhao; Nengbin Cai; Xiaochun Huang; Wenbin Liu (Journal of Saudi Chemical Society, 2017)
We report on a novel, green, and efficient organically synthetic method for the preparation of gold nanoparticles embedded in mesoporous silica (AuNPs@mesoSiO2). AuNPs@mesoSiO2 prepared by one-pot synthesis method using sodium citrate as the key reactant was applied for surface enhanced Raman spectroscopy (SERS) application in the analysis of diluted blood traces. The synthesized nanoparticles are of high quality, as characterized by use of X-ray diffraction, scanning electron microscopy and transmission electron microscopy. They exhibit high surface areas (170.18â883Â m2/g) and significant SERS enhancement. Detection of diluted blood (v/v, 1:50) traces through AuNPs@mesoSiO2 enhanced SERS is demonstrated, which has not been studied in previous literature. The combination of the SERS and AuNPs@mesoSiO2 would be a valuable tool for forensic investigation. Keywords: Gold nanoparticles, Mesoporous materials, Synthesis, SERS, Blood trace